Characterization and Biocontrol Efficacy of Bacillus velezensis GYUN-1190 against Apple Bitter Rot - Hyeonjin Park; Younmi Lee; Kotnala Balaraju; Jungyeon Kim; Yongho Jeon (The Plant Pathology Journal, 2024)
The application of synthetic fungicides has resulted in environmental pollution and adverse effects on non-target species. To reduce the use of agrochemicals, crop disease management requires microbial biological control agents. Bacillus-related genera produce secondary metabolites to control fungal pathogens. Bacillus velezensis GYUN-1190, isolated from soil, showed antagonistic activity against Colletotrichum fructicola, the apple anthracnose pathogen. Volatile organic compounds and culture filtrate (CF) from GYUN-1190 inhibited C. fructicola growth in vitro, by 80.9% and 30.25%, respectively. The CF of GYUN-1190 inhibited pathogen spore germination more than cell suspensions at 108 cfu/ml. Furthermore, GYUN-1190 CF is effective in inhibiting C. fructicola mycelial growth in vitro, and it suppresses apple fruit bitter rot more effectively than GYUN-1190 cell suspensions and pyraclostrobin in planta. The mycelial growth of C. fructicola was completely inhibited 48 h after immersion into the CF, in compared with positive controls and GYUN-1190 cell suspensions. The genetic mechanism underlying the biocontrol features of GYUN-1190 was defined using its whole-genome sequence, which was closely compared to similar strains. It consisted of 4,240,653 bp with 45.9% GC content, with 4,142 coding sequences, 87 tRNA, and 28 rRNA genes. The genomic investigation found 14 putative secondary metabolite biosynthetic gene clusters. The investigation suggests that B. velezensis GYUN-1190 might be more effective than chemical fungicides and could address its potential as a biological control agent.